Identification of phenomena occurring in porous structure of cement concrete subjected to cyclic freezing and thawing - Lelusz, Małgorzata; Malaszkiewicz, Dorota (Journal of Civil Engineering and Management, 2004)
The influence of cyclic freezing and thawing of concrete upon its microstructure is investigated in this research. The following methods were applied: microscope analysis of specially prepared fragments of concrete specimens, capillary pulling up water under atmospheric pressure, thermal analysis of hardened cement paste separated from concrete specimens. Tested concrete did not contain any chemical or mineral admixtures; W/C ratio was constant for all specimens (0,65). Indexes of mean radius of capillary pores ‐ λ and indexes of homogeneity of capillary pores ‐ α were measured after various numbers of freezing cycles. Experimental results enable to describe the phenomena occurring in concrete subjected to frost.First Published Online: 14 Oct 2010